Differential effects of high dose omega-3 fatty acids on metabolism and inflammation in patients with obesity: eicosapentaenoic and docosahexaenoic acid supplementation - Borja-Magno, Angélica; Guevara-Cruz, Martha; Flores-López, Adriana; Carrillo-Domínguez, Silvia; Granados, Julio; Arias, Clorinda; Perry, Mary; Sears, Barry; Bourges, Hector; Gómez, F. Enrique (Frontiers in Nutrition, 2023)
Background: Obesity is complicated by low-grade chronic inflammation characterised by increases in inflammatory proteins and cells in peripheral blood. It has been known that omega-3 fatty acids (FA) like eicosapentaenoic (EPA) and docosahexaenoic (DHA) could modulate the inflammatory process and improve metabolic markers. Objective: This study aimed to determine the effect of high-dose omega-3 FA on metabolic and inflammatory markers among patients with obesity and healthy volunteers. Methods: This prospective study included 12 women with obesity (body mass index [BMI] ≥ 35.0 kg/m2) and 12 healthy women (BMI ˂ 24.0 kg/m2) who were supplemented with a dose of 4.8 g/day (3.2 g EPA plus 1.6 g DHA) for 3 months followed by no treatment for one month. Plasma metabolic and inflammatory markers and levels of mRNA transcripts of CD4+ T lymphocyte subsets were determined monthly. Results: None of the participants exhibited changes in weight or body composition after study completion. EPA and DHA supplementation improved metabolic (insulin, Homeostatic Model Assessment of Insulin Resistance [HOMA-IR], triglyceride [TG]/ high-density lipoprotein [HDL] ratio, TG, and arachidonic acid [AA]/EPA ratio) and tumor necrosis factor-alpha (TNF-). Moreover, the levels of mRNA transcripts of T CD4+ lymphocyte subsets (TBX21, IFNG, GATA-3, interleukin [IL]-4, FOXP3, IL-10 IL-6, and TNF-), were down-regulated during the intervention phase. After one month without supplementation, only insulin, HOMA-IR and the mRNA transcripts remained low, whereas all other markers returned to their levels before supplementation. Conclusion: Supplementation with high-dose omega-3 FAs could modulate metabolism and inflammation in patients with obesity without weight loss or changes in body composition. However, these modulatory effects were ephemeral and with clear differential effects: short-duration on metabolism and long-lasting on inflammation.